2015
DOI: 10.1136/archdischild-2014-307997
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemic urinary tract infection: management and outcomes in young infants

Abstract: Parenteral antibiotic treatment duration in young infants with bacteraemic UTI was variable and only minimally explained by measurable patient factors. Relapses were rare and were not associated with treatment duration. Shorter parenteral courses may be appropriate in some infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 26 publications
4
43
0
5
Order By: Relevance
“…While the risk of bacteremia secondary to UTI remains substantial, it is unlikely to be associated with adverse effects, and recent studies on well‐appearing infants with bacteremia secondary to UTI show similar clinical outcomes between those treated with a prolonged course of parenteral antibiotics vs. those treated with shorter courses of parenteral antibiotics [17, 30, 31]. …”
Section: Epidemiology Of Infections In Febrile Infantsmentioning
confidence: 99%
“…While the risk of bacteremia secondary to UTI remains substantial, it is unlikely to be associated with adverse effects, and recent studies on well‐appearing infants with bacteremia secondary to UTI show similar clinical outcomes between those treated with a prolonged course of parenteral antibiotics vs. those treated with shorter courses of parenteral antibiotics [17, 30, 31]. …”
Section: Epidemiology Of Infections In Febrile Infantsmentioning
confidence: 99%
“…The prevalence of bacteremia in infants ≤60 days old with UTIs was 9% in a study conducted from 2008 to 2013 in 26 EDs and has ranged from 3% to 17% in older studies. 10,22 Many studies have described similar clinical and laboratory findings in young infants with bacteremic and nonbacteremic UTIs. [39][40][41] Despite this, bacteremic UTIs have been associated with prolonged parenteral antibiotic courses, resulting in longer hospitalizations and increased costs.…”
Section: Special Considerations Bacteremic Utimentioning
confidence: 94%
“…[39][40][41] Despite this, bacteremic UTIs have been associated with prolonged parenteral antibiotic courses, resulting in longer hospitalizations and increased costs. 40 Two recent multicenter studies of infants with bacteremic UTIs (251 infants <3 months old 22 and 115 infants ≤60 days old 42 ) demonstrated variable IV courses and no association between IV duration and relapsed UTI. The latter study showed no risk difference in the adjusted 30-day UTI recurrence (risk difference 3%, 95% CI: −5.8 to 12.7) or allcause reutilization (risk difference 3%, 95% CI: −14.5 to 20.6) between long and short IV groups.…”
Section: Special Considerations Bacteremic Utimentioning
confidence: 99%
See 1 more Smart Citation
“…The linked study by Schroeder et al 4 shows marked variation in the duration of parenteral antibiotics given by paediatricians to treat infants with bacteraemic UTIs in 11 US centres. The duration of parenteral antibiotics mostly seemed to depend on local practice, with each institution having a different mean duration (5, 7, 10 or 12 days).…”
mentioning
confidence: 99%